Drowned and dammed colonial capitalism and flood control in Eastern India - D'Souza, Rohan (Oxford University Press, 2006)
Exploring the practice of flood control, this work argues that this is a part of a political agenda, implicated in the calculations of capitalism. It also argues for a reconsideration of the debate on the colonial environmental watershed, its hydraulic legacy and questions contemporary enthusiasm for flood control in post-independent India